2017
DOI: 10.5194/amt-10-4687-2017
|View full text |Cite
|
Sign up to set email alerts
|

Effects of gas–wall partitioning in Teflon tubing and instrumentation on time-resolved measurements of gas-phase organic compounds

Abstract: Abstract. Recent studies have demonstrated that organic compounds can partition from the gas phase to the walls in Teflon environmental chambers and that the process can be modeled as absorptive partitioning. Here these studies were extended to investigate gas-wall partitioning of organic compounds in Teflon tubing and inside a protontransfer-reaction mass spectrometer (PTR-MS) used to monitor compound concentrations. Rapid partitioning of C 8 -C 14 2-ketones and C 11 -C 16 1-alkenes was observed for compounds… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
184
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(209 citation statements)
references
References 35 publications
(51 reference statements)
5
184
2
Order By: Relevance
“…As a reference point, the response delay due to the use of 30-meter-long tubes was estimated to be 0.8 minutes for nonanal (C 9 H 18 O) at this flow rate. 33 Two different sampling sequences were employed for gas measurements during observational monitoring. During most periods, data were collected with spatial resolution emphasized, switching regularly at 5-minute intervals among each of the six inlets (ie, 30 minutes for one full cycle).…”
Section: Observational Campaignmentioning
confidence: 99%
“…As a reference point, the response delay due to the use of 30-meter-long tubes was estimated to be 0.8 minutes for nonanal (C 9 H 18 O) at this flow rate. 33 Two different sampling sequences were employed for gas measurements during observational monitoring. During most periods, data were collected with spatial resolution emphasized, switching regularly at 5-minute intervals among each of the six inlets (ie, 30 minutes for one full cycle).…”
Section: Observational Campaignmentioning
confidence: 99%
“…3.3.1), inlet losses of highly volatile compounds were negligible, but we were not able to quantify possible losses of less volatile compounds. Measurement of compounds with saturation vapor pressure (C 0 ) less than 10 5 µg m −3 may be affected (Pagonis et al, 2017). A slight delay in the instrument response to some compounds with C 0 close to 10 4 µg m −3 was observed.…”
Section: Ptr-tof and Nomentioning
confidence: 99%
“…Many more IVOC species have been measured by 2-D-GC (Hatch et al, 2017). It is expected that many species of C 0 < 10 4 µg m −3 were not transmitted through the transfer inlet and instrument tubing quickly enough to be quantifiable by the PTR-MS (Pagonis et al, 2017).…”
Section: Emission Factors Emission Ratios and Emission Chemistrymentioning
confidence: 99%
“…The accommodation coefficient on Teflon is orders of magnitude lower than 0.1 [35,36], but to our knowledge, no literature data on wall accommodation coefficients on stainless steel exist. Pagonis et al [37] investigated the effect of partitioning between gas and Teflon tubing for several VOCs, and found that significant delays due to the retention times could occur. The time-scales for equilibrium partitioning in the inlet is unknown, but the duration of the measurements, together with the PTR-MS measurements, favors the conclusion that the lack of reactor SOA production was not due to VOC losses.…”
Section: Resultsmentioning
confidence: 99%